Orfeus i telefonhytten: Proust, hörseln och det moderna - Danius, Sara (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2012)
For a theory of the relation between late-nineteenth-century technology and perceptual experience, one could use as a starting-point Karl Marx’s proposition that the human senses have a history. One could also draw on the theory of perceptual abstraction and sensory autonomization implicit in the writings of Walter Benjamin, Guy Debord, Paul Virilio, Marshall McLuhan, Friedrich Kittler, and Michel Chion. As this essay suggests, however, one would do equally well to begin with Marcel Proust. Indeed, in a central episode in the third volume of A la recherche du temps perdu (1913-1927), Proust offers a psychology of technological change that may be grasped as a theory in its own right. More specifically, it is a theory of how the emergence of technologies for transmitting sound such as the telephone paves the way for a new matrix of perception, in which not only sound but also vision turn into abstract and autonomous phenomena. As a result, the perceptual habits of the eye and the ear begin to function separately, each independent of the other. In addition, the autonomization of the ear is inherent in that of the eye, and vice versa. The essay also considers the importance of the telephone in Sigmund Freud and Walter Benjamin.